Preservation of the immunomodulatory effect of interval hypoxytherapy after coronavirus infection in the long-term period - I. Kh. Borukaeva; Z. Kh. Abazova; A. B. Ivanov; I. A. Misirova; K. Yu. Shkhagumov; F. V. Shavaeva; A. A. Mоlov; T. B. Kipkeeva; A. G. Shokueva (Медицинская иммунология, 2023)
The new coronavirus infection COVID-19, due to the complex pathogenesis of the disease, systemic impact on organs, the development of complications and persistent disorders after the infection, remains an important medical problem. Every year the number of patients with postcovid syndrome in need of timely and full rehabilitation is increasing. Recently, isolated work began to appear on the use of interval hypoxytherapy for the treatment of patients with coronavirus infection. The purpose of our study was to identify the long-term results of the effect of interval hypoxytherapy on the immunological and coagulation status of patients after suffering coronavirus infection COVID-19. 170 patients aged 45 to 59 years were examined after a moderate coronavirus infection before, after and three months after interval hypoxytherapy. The number of lymphocytes, immunoglobulins A, M, G, E and cytokines (IL-1β, IL-2, IL-4, IL-6, IL-8, IL-10, TNFα) in blood, blood D-dimer, prothrombin time, fibrinogen in blood, antithrombin III, C-reactive was determined protein and ferritin in the blood. The conducted studies revealed changes in immunological reactivity after the coronavirus infection COVID-19, requiring correction. Interval hypoxytherapy had an immunomodulatory effect and led to the normalization of the main immunological parameters, which remained three months after hypoxytherapy: there was a significant (p < 0.05) increase in the number of CD3+T lymphocytes, CD4+T lymphocytes, CD8+T lymphocytes. The improvement in immune status was also evidenced by the normalization of the immunoregulatory index, an increase in the level of immunoglobulins A and G. The decrease in immunoglobulins E in the blood was an indicator of a decrease in the severity of sensitization of the body. The course of hypoxytherapy led to a decrease in the content of pro-inflammatory cytokines: IL-1β, IL-2, IL-6, IL-8, TNFα and an increase in anti-inflammatory cytokines: IL-4 and IL-10 in the blood, which indicated an attenuation of the inflammatory process in the lung tissue and in the body as a whole. Blood ferritin decreased 3 months after hypoxytherapy. As studies have shown, the effect of hypoxytherapy persists for three months after the course of treatment. Thus, interval hypoxytherapy can be recommended for the rehabilitation of patients after a moderate coronavirus infection. A repeated course of hypoxytherapy may be performed three months after the first course of hypoxytherapy.